Mortality in a cohort of asbestos-exposed workers undergoing health surveillance - Barbiero, Fabiano; Zanin, Tina; Pisa, Federica Edith; Casetta, Anica; Rosolen, Valentina; Giangreco, Manuela; Negro, Corrado; Bovenzi, Massimo; Barbone, Fabio (La Medicina del Lavoro, 2018)
Background: The coastal area of Friuli Venezia Giulia (FVG) region, north-eastern Italy, was characterized by work activities in which asbestos was used until the early 1990s, particularly in shipbuilding. A public health surveillance program (PHSP) for asbestos-exposed workers was established, although limited evidence exists about the efficacy of such programs in reducing disease occurrence and mortality. Objectives: To compare mortality in a cohort of 2,488 men occupationally exposed to asbestos, enrolled in a PHSP in FVG between the early 1990s and 2008, with that of the general population of FVG and Italy. Methods: Standardized Mortality Ratios (SMR), with 95% Confidence Interval (95% CI), for all causes, all cancers, lung (LC) and pleural cancer (PC) were estimated in the cohort and in subgroups of workers with the first hire in shipbuilding that caused asbestos exposure (